Suggested Algorithm For Speech Signal Coding - khalil Al saif; Saja Mohammed (College of Education for Pure Sciences, 1970)
Abstract This paper discusses a suggested approach for new kind of Speech Signal Compression Algorithm based on KL transform (Karhunen-Loève transform) which normally used with digital image. Speech signal (which is single sequence) rearranged in form of two dimension square matrix to be suitable for KL transformation. Then to be compressed using different no. of eigen values and eigenvectors. Measuring the performance of applied KL transformation (by evaluating the PSNR and SNR factors) with different numbers of eigen values and vectors studied. High rate of compression with high SNR, PSNR got with so closed speech signal to the original one measured using correlation factor which gives values near to 1. In addition to short time needed for compression operation.